Effects of Row Spacing, Seeding Rate, and Planting Date on Establishment of Switchgrass. Issue 1 (1st January 2013) - Foster, Jamie L.; Guretzky, John A.; Huo, Chengjun; Kering, Maru K.; Butler, Twain J.
Abstract : Switchgrass ( Panicum virgatum L.) has been identified as a potential biomass crop for marginal cropland, but establishment can be problematic. In Exp. 1, treatments (seeding rate and row spacing) were arranged as a randomized complete block in a split‐plot design with four replicates in which the main plot treatment was row spacing (17.8, 35.6, 71.1, or 88.9 cm) and the subplot treatment was seeding rate (1.12, 2.24, 3.36, or 4.48 kg pure live seed [PLS] ha −1 ). In Exp. 2, treatments (seeding rate and planting date) were arranged as a randomized complete block in a split‐split‐plot design with four replicates in which the main plot treatment was planting date (September, February, or May), the subplot treatment was switchgrass ecotype (upland 'Cave‐in‐Rock' or lowland 'EG1101'), and the sub‐subplot was seeding rate (2.24, 4.48, 6.72, 8.96, or 11.20 kg PLS ha −1 ). In Exp. 1, row spacing did not affect seedling density, but switchgrass at the widest row spacing (88.9 cm) produced the least dry matter (DM) yield during the establishment year. However, row spacing had no effect on DM yield after the establishment year. In Exp. 2, increasing seeding rate increased seedling density but had no effect on DM yield. In addition, seedling density was greatest for both ecotypes planted in September; however, February‐ and May‐planted EG1101 produced the greatest DM yield. While upland switchgrass may be successfully planted in autumn in the southern Great Plains, lowland switchgrass should be planted only in the spring because of seedlings' susceptibility to freezing.